Analisis Beban Kerja Fisiologis Karyawan di Lantai Produksi PT. XYZ: Mengungkap Dampaknya terhadap Kinerja dan Kesehatan - ALIUS, MUTIA (-, 2025)
This study analyzes the physiological workload of employees in the production floor of PT. XYZ, a company specializing in tuna export. The manual production process requires workers to stand for four hours without rest, potentially leading to physical and mental fatigue. The research methodology includes heart rate measurement, energy consumption analysis, and Cardiovascular Load (CVL) calculation to assess worker fatigue levels. The findings indicate that most employees experience a light workload, with CVL values below 30%, meaning no excessive fatigue. However, the fish-cutting activity presents the highest workload compared to other workstations. Based on these results, task rotation and work system improvements are recommended to enhance employee well-being and productivity.